Digital-Based MSME Empowerment Strategy and Local Economic Strengthening: An SEM Approach in Medan City - Nst, Venny Fraya Hartin; Gultom, Lilis S; Pangabean, Nazla Rachma (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2026)
Micro, Small, and Medium Enterprises (MSMEs) serve as key pillars of Indonesia’s economic development, significantly contributing to employment, income equity, and Gross Domestic Product (GDP) growth. However, in the digital economy era, many MSMEs continue to struggle with structural barriers such as low digital literacy, inadequate technological infrastructure, limited financing access, and weak digital marketing capabilities. This study aims to examine digital-based empowerment strategies for strengthening the local economy in Medan City. Employing a quantitative research design through a survey method, data were collected from MSME actors and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The findings reveal that digital literacy (β = 0.65, p < 0.01), digital infrastructure (β = 0.58, p < 0.01), and policy support (β = 0.60, p < 0.01) significantly influence technology adoption, which subsequently enhances digital marketing strategies (β = 0.62, p < 0.001) and MSME performance (β = 0.72, p < 0.001). Digital marketing strategy emerges as the most influential factor (β = 0.80, p < 0.001), with strong explanatory power (R² = 0.68 for technology adoption; R² = 0.74 for MSME performance). The results indicate that successful MSME digital transformation requires not only technical competence but also an enabling ecosystem involving policy support, infrastructure readiness, and continuous digital training. The study recommends integrated empowerment initiatives through digital literacy education, fiscal incentives, fintech access, QRIS adoption, and e-commerce partnerships to enhance MSME competitiveness and economic resilience in Medan’s digital transformation era.